2023
DOI: 10.1002/agt2.360
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation‐induced emission artificial enzyme (AIEzyme) with DNase‐like activity: Imaging and matrix cleavage for combating bacterial biofilm

Abstract: DNase‐catalyzed hydrolysis of extracellular DNA (eDNA) has been widely employed to eradicate intractable biofilms. Although aggregation‐induced emission (AIE) has become the ideal tool for killing planktonic bacteria, AIE luminogens (AIEgens) often lack DNase‐mimetic activity, so as to suffer from poor anti‐biofilm capacity. Here, an “AIEzyme”, a kind of AIE nanomaterial with enzyme‐like activity, is designed and synthesized, where the AIEgens are used as the ligands of Zr‐based coordination polymer nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…10–15 Among them, nanocatalytic cancer therapy (NCT) employs nanozymes with the advantages of nanomaterials and natural enzymes to catalyze hydrogen peroxide decomposition for the production of highly cytotoxic ROS, which can achieve a desirable therapeutic effect. 16–19 Compared to natural enzymes, nanozymes have the advantages of being low-cost, highly stable, adjustable, and easily produced in large quantities, making them more efficient and reliable even in harsh environments. 20–22 Many nanozymes, such as noble metals, metal oxides or sulfides, metal–organic frameworks, and carbon-based nanomaterials, have been reported to imitate the functions of natural peroxidase (POD), catalase (CAT), and glutathione peroxidase (GSH-px), exhibiting TME regulation abilities for amplified ROS production.…”
Section: Introductionmentioning
confidence: 99%
“…10–15 Among them, nanocatalytic cancer therapy (NCT) employs nanozymes with the advantages of nanomaterials and natural enzymes to catalyze hydrogen peroxide decomposition for the production of highly cytotoxic ROS, which can achieve a desirable therapeutic effect. 16–19 Compared to natural enzymes, nanozymes have the advantages of being low-cost, highly stable, adjustable, and easily produced in large quantities, making them more efficient and reliable even in harsh environments. 20–22 Many nanozymes, such as noble metals, metal oxides or sulfides, metal–organic frameworks, and carbon-based nanomaterials, have been reported to imitate the functions of natural peroxidase (POD), catalase (CAT), and glutathione peroxidase (GSH-px), exhibiting TME regulation abilities for amplified ROS production.…”
Section: Introductionmentioning
confidence: 99%
“…With continuous in-depth research, the mechanism of the AIE phenomenon was revealed: the restriction of intramolecular motion (RIM) played a key role in the AIE phenomenon . In recent years, various aggregation-induced emission luminogens (AIEgens) have been developed for wide areas, such as photopatterning, bioimaging, biosensors, antibacterial agents, and biomedical therapy. However, the vast majority of AIEgens commonly suffer from complex organic synthesis, high cost of environmental damage, and potential biological toxicity. ,, More crucially, AIEgens generally can aggregate and emit strong fluorescence in an aqueous solution because of poor water solubility. , However, in many cases of biosensing, what we need is that the fluorophore should not emit light in an aqueous solution, even containing DNA and other biomacromolecules, until the target biomolecules are added. Therefore, it is particularly important to explore new environmentally friendly, biocompatible, and water-soluble AIEgens.…”
Section: Introductionmentioning
confidence: 99%
“…5 With continuous in-depth research, the mechanism of the AIE phenomenon was revealed: the restriction of intramolecular motion (RIM) played a key role in the AIE phenomenon. 6 In recent years, various aggregationinduced emission luminogens (AIEgens) have been developed for wide areas, such as photopatterning, 7 bioimaging, 8 biosensors, 9 antibacterial agents, 10 and biomedical therapy. 11−13 However, the vast majority of AIEgens commonly suffer from complex organic synthesis, high cost of environmental damage, and potential biological toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nanozymes are nanomaterials with an enzyme-like property. So far, diverse nanozymes including DNase-like nanozyme, peroxidase (POD) and oxidase, have been developed for antibacterial therapy due to their specific antibacterial mechanism, easy preparation, and low price. , Tang et al designed an aggregation-induced emission nanozyme with DNase-like property, which could damage the integrality of biofilms and promote the wound healing process . In recent years, POD-like nanozymes have displayed great potential for bacterial eradication.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Tang et al designed an aggregation-induced emission nanozyme with DNase-like property, which could damage the integrality of biofilms and promote the wound healing process. 7 In recent years, POD-like nanozymes have displayed great potential for bacterial eradication. Numerous studies have demonstrated that the POD-like nanozyme realized the antibacterial performance by converting hydrogen peroxide (H 2 O 2 ) into extremely toxic hydroxyl radicals (•OH).…”
Section: Introductionmentioning
confidence: 99%